The runaways - Snyder, Zilpha Keatley (New York : Dell Yearling, 2000)
Twelve-year-old Dani hates living in the small desert town of Rattler Springs, Nevada, but her plans to run away get complicated when a pesty young boy and an imaginative new girl decide they want to go along.
Keywords: Parent and child -- Juvenile fiction; Missing children -- Juvenile fiction; Nevada -- Juvenile fiction